P185 Characteristics of safety in a national sample of small businesses. (1st September 2016) - Parker, David; Yamin, Samuel
Abstract : Background: Small enterprises represent a significant portion of the United States economy. Nearly 98% of the 4.9 million U.S. businesses have fewer than 100 employees; those account for 36% of all employment. These manufacturing businesses often lack important safety programs. Many reasons have been set forth on why this has remained a persistent problem. Methods: The National Machine Guarding Program (NMGP) was a nationwide intervention conducted in partnership with two workers' compensation insurers. Insurance safety consultants collected baseline data in 221 business using a 33-question safety management audit. Audits were completed during an interview with the business owner or manager. Four scores were computed for each business: an overall safety management audit score, safety leadership, job hazard analysis, machine maintenance, and lockout and tagout (LOTO). Results: Most measures of safety management improved with an increasing number of employees. This trend was particularly strong for lockout/tagout. Establishments with a safety committee scored higher (55% v 36%) on the safety management audit compared with those lacking a committee (p < 0.0001). For the safety leadership program, scores improved significantly with increasing shop size for 7 out of 12 checklist items. Businesses with 50 to 150 employees typically had the most program components in place. There was a significant trend between the smallest and largest shops for the presence of a safety committee (p < 0.0001); its presence went from 21% in the smallest shops to 77% in the largest. Larger shops were also significantly more likely than their smaller peers to have written policies for reporting injuries, discipline for failing to follow safety procedures, and formalised methods for obtaining employee input on safety issues. Conclusions: Critical safety management programs were frequently absent. A safety committee appears to be a more important factor than business size in accounting for differences in outcome measures.